Depth and luminance edges attract - Robinson, Alan E. (The Association for Research in Vision and Ophthalmology, 2013)
The spatial resolution of disparity perception is poor compared to luminance perception, yet we do not notice that depth edges are more blurry than luminance edges. Is this because the two cues are combined by the visual system? Subjects judged the locations of depth-defined or luminance-defined edges, which were separated by up to 5.6 min of arc. The perceived edge location was a function of the depth-defined edge and the luminance-defined edge, with the luminance edge tending to play a larger role. Our data are compatible with but not completely explained by an optimal cue-combination model that gives more reliable cues a heavier weight. Both edge cues (depth and luminance) contribute to the final percept, with an adaptive weighting depending on the task and the acuity with which each cue is perceived.